BRAND PERSONALITY MATTERS: ENHANCING CUSTOMER LOYALTY IN THE RETAIL INDUSTRY - Luluk Fauziah; Agus Dedi Subagja; Putri Anditasari; Yogi Syarif Hidayat; Yusti Pujisari (UIN Sunan Gunung Djati Bandung, 2023)
Customers are an important part of a company. Therefore, customer loyalty is an important aspect that needs to be obtained by the Company. One of the steps to increase customer loyalty is through brand personality. This study aims to see how brand personality can increase customer loyalty. This research will be carried out with a descriptive qualitative approach. The data used in this study comes from various research results and previous studies. The results of this study then found that brand personality is an important factor in building customer loyalty. Through an attractive brand personality, customers will feel personally connected to the brand, where which will then increase trust and cause purchasing decisions to be more consistent.